Scheduling GnRH antagonist cycles by a short course of oral estradiol administration during early follicular phase: a comparative study with non-scheduled cycles. (June 2015) - Aslan, Kiper; Avci, Berrin; Uncu, Gurkan; Saribal, Seda; Ata, Baris
Abstract This hypothesis generating study investigated whether GnRH antagonist cycles can be scheduled by a short course of oral estradiol administration during the follicular phase without impairing treatment outcome. Thirty-five women who underwent follicular phase estrogen scheduling (ES) of GnRH antagonist cycles were retrospectively matched for age and number of prior failed cycles with 35 women who underwent unscheduled GnRH antagonist cycles. ES group was given 6 mg/day estradiol orally from cycle day 2 until (including) one day before the scheduled start of stimulation. Gonadotropins were started on cycle days 2–3 in the control group. Flexible GnRH antagonist protocol was employed in both groups. ES group received estradiol for a median of 5 days. Total gonadotropin consumption was similar but one more GnRH antagonist injection was required in the ES group. Endometrial thickness on the day of hCG injection was increased in the ES group (12 versus 10 mm, p < 0.01). Number of oocytes, metaphase II oocytes and transferred embryos were similar. Embryo implantation rates were 44.8% versus 34.4% (p = 0.3), and clinical pregnancy rates were 48.6% versus 37.1%, (p = 0.33) in the ES and control groups, respectively. All women in the ES group had oocyte retrieval and embryo transfer within the desired period.